International financial centers as the «heart» of the global financial market - Шуба, Марина (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism)
<span style="font-size: 14.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: MinionPro-Regular; mso-ansi-language: EN-US; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="EN-US">The article studies<span style="font-size: 14.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: MinionPro-Regular; mso-ansi-language: UK; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="UK"> factors and conditions that contribute to the emergence of international financial centres. The role of international financial centers in the development of global financial market are considered, trends in their development are identified. The most famous international rankings of the <span style="font-size: 14.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: MinionPro-Regular; mso-ansi-language: EN-US; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="EN-US">world<span style="font-size: 14.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: MinionPro-Regular; mso-ansi-language: UK; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="UK"> financial centers are analyzed.